Effect of nitridation and carburization of γ-TiAl alloys on wear resistance - Boonruang C. (2014)
The 1000-1300 K nitridation and carburization processes of MJ12 (Ti-47Al-2Nb-2Cr) and MJ47 (Ti-47Al-2Nb-2Mn+0.8TiB2) were studied in the purified ammonia and acetylene. Flow rate of the ammonia was kept constant at 10 cm3 s-1 and that of the acetylene was kept at 0.01, 0.03 and 0.05 cm3 s-1. The properties of the alloys were extensively analyzed. The Knoop hardness values were increased with increase in temperature and acetylene potential. A WC pin-on-disk wear rate was reduced by one or two orders of magnitude in comparison with the untreated alloys. In addition, the surfaces of the alloys were characterized using the XRD, SEM and EDX analyzers to determine the new phases formed. © 2004 Elsevier B.V. All rights reserved.